Complete Hypnotism, Mesmerism, Mind-Reading and Spiritualism : How to Hypnotize: Being an Exhaustive and Practical System of Method, Application, and Use - Alpheus, A. (Salt Lake City, UT : Project Gutenberg, 2006)
"Complete Hypnotism, Mesmerism, Mind-Reading and Spiritualism" by A. Alpheus is a scientific publication written in the early 20th century. The book explores various aspects and methods of hypnotism, mesmeric practices, and the interrelation of mind-reading and spiritualistic phenomena. Alpheus discusses historical figures and theories surrounding hypnotism, including notable practitioners like Mesmer and Braid, and offers practical instructions for inducing hypnotic states. The opening of the work introduces the concept of hypnotism as an ancient practice that has evolved over centuries, detailing its cultural and historical background. It highlights the significant contributions of key figures in the field, such as Mesmer's animal magnetism theory and Braid's method of inducing hypnotism through concentration. A. Alpheus sets the stage for understanding hypnotism not only as a fascinating psychological phenomenon but also as a tool for healing and exploration of the mind, promising insights and practical knowledge in the subsequent chapters. (This is an automatically generated summary.)
Release date is 2006-09-20
Jerry Kuntz
Keywords: Spiritualism; Hypnotism; Telepathy; Mesmerism